Stakeholder Engagement and Sustainable Corporate Community Investment - Rowe, Anna; Nowak, Margaret; Quaddus, Mohammed; Naude, Marita (Wiley Interscience, 2013)
This paper presents the findings of research exploring the value and impacts of corporate community investment (CCI) through community partnerships. The research considered the community partners' perceptions of the value and impact of CCI. We adopted an inquiry paradigm utilising constructivist ontology, interpretivist epistemology and a case study method. In dialogue with Wesfarmers Ltd's community partners, the ‘realities’ presented by these beneficiary stakeholders were interpreted and understood (verstehen).While the CCI programmes with each of the not-for-profit organisations had different objectives, we were able to classify, under broad headings, the nature of the benefits to the community. One question highlighted is whether all corporate investing is the same? We found two aspects to this: the strategic fit for the community organisation of proposed investment and whether the corporate partner sought a relational as opposed to transactional approach to funding provision. Recommendations can be made for the funding structure deemed to be most effective from the community partners' perspectives.